2002
DOI: 10.1016/s0886-3350(01)01319-0
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic protection from endothelial damage by air bubbles

Abstract: Viscoat effectively protected the endothelium from air-bubble damage. Viscoat appears to protect the endothelium by acting as a physical barrier. Its adherence is probably related to the way it interacts with the mucinous layer of the endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
20
0
4
Order By: Relevance
“…In this study, the density of corneal endothelial cells decreased following cataract surgery when compared with the preoperative numbers in both groups. In previous studies, to analyze the degree of corneal damage following phacoemulsification, the number and density of corneal endothelial cells in a 1 mm 2 area were measured using specular microscopy [16][17][18][19]; however, specular microscopy can only evaluate a small part of the corneal endothelial injury and is therefore insufficient for ascertaining changes in the entire cornea and morphological changes at the incision point. Therefore, based on the central corneal thickness and specular microscopy alone, the data needed for determining the degree of corneal edema following phacoemulsification are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the density of corneal endothelial cells decreased following cataract surgery when compared with the preoperative numbers in both groups. In previous studies, to analyze the degree of corneal damage following phacoemulsification, the number and density of corneal endothelial cells in a 1 mm 2 area were measured using specular microscopy [16][17][18][19]; however, specular microscopy can only evaluate a small part of the corneal endothelial injury and is therefore insufficient for ascertaining changes in the entire cornea and morphological changes at the incision point. Therefore, based on the central corneal thickness and specular microscopy alone, the data needed for determining the degree of corneal edema following phacoemulsification are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell loss after phacoemulsification surgery is well documented. 6,7 Corneal endothelial damage during phacoemulsification is attributed to several factors including excessive duration of phacoemulsification, [8][9][10] localized temperature increase, 11 contact or collision of lens nucleus fragments after turbulent flow of irrigation solution, 12,13 air bubbles, 14,15 and surgical skills. 16 It has also been shown that the generation of free radicals during phacoemulsification can cause adverse effects on the cellular and subcellular levels through diverse mechanisms, one of which is acoustic cavitation.…”
mentioning
confidence: 99%
“…Corneal endothelium damage in phacoemulsification is caused by several factors including excessive duration of phacoemulsification, 1-3 localized temperature increase, 4 contact or collision of lens nucleus fragments following the turbulent flow of the irrigation solution, 5,6 or air bubbles. 7,8 Although it is not widely recognized, another harmful factor associated with the use of ultrasound (US) is the development of free radicals. Free radicals can cause oxidative damage to endothelial cells, and their presence may be 1 of the most damaging events during these procedures.…”
mentioning
confidence: 99%